The inverse of a function f(x) is f⁻¹(x) = 4x + 3 after using the concept of the inverse of a function.
It is defined as a special type of relationship, and they have a predefined domain and range according to the function every value in the domain is related to exactly one value in the range.
We have a function:
[tex]\rm f(x) = \dfrac{1}{4}x-\dfrac{3}{4}[/tex]
To find the inverse of a function:
Interchange the f(x) and x
f(x) → x
x → f⁻¹(x)
[tex]\rm x = \dfrac{1}{4}f^{-1}(x)-\dfrac{3}{4}[/tex]
Make the subject f(x);
[tex]\rm \dfrac{1}{4}f^-^1(x)=x+\dfrac{3}{4}[/tex]
[tex]\rm f^-^1(x)=4x+3[/tex]
Thus, the inverse of a function f(x) is f⁻¹(x) = 4x + 3 after using the concept of the inverse of a function.
Learn more about the function here:
brainly.com/question/5245372
#SPJ1